Examen especial al activo corriente de la empresa “I.M.C. Ruilova CIA. LTDA” de la ciudad de Loja, período 2021 - Viñamagua Puglla, Irma del Rocío (2023)
The present Work of Curricular Integration denominated Special Examination to the Current Assets of the Company "I.M.C. RUILOVA CIA. LTDA" of the city of Loja, period 2021, was elaborated under the Academic Regulations of the National University of Loja, as a prerequisite to obtain the degree of Bachelor in Accounting and Auditing. To meet the proposed objectives the quantitative and qualitative methodology was applied and the audit phases oriented to the special examination which are; Phase I, Planning, began with a previous visit to the company, obtaining a general approach of the Company LTDA. "I.M.C. RUILOVA" facilitating the drafting of the preliminary and specific planning report, making known the activities carried out by the company. Phase II, Execution; substantive and control procedures were applied to the accounts examined and reflected in the audit program, internal control was evaluated and the respective tests were applied, supported by evidence based on audit criteria, Phase III; Communication of Results, a final report was prepared containing comments, conclusions and recommendations aimed at taking the necessary corrective measures to help meet the goals and objectives. The main results obtained show internal control weaknesses such as: irregularities in the bank account, absence of surprise cash audits, lack of surety bonds for the personnel in charge of handling financial resources; it does not guarantee security in the reliable handling of the Company's cash. In addition, it was determined that there are no internal control regulations and standards that determine the obligations and responsibilities that employees must comply with.